2020
DOI: 10.1016/j.archoralbio.2019.104633
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of total salivary lipopolysaccharide chemical and biological properties with periodontal status

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Given this, we can do a case/control differential analysis for OralUreaseActivityPathways in our independent validation cohort. Here, “case” samples are defined using an aggregate of multiple systemic disease phenotypes which are based on reported associations to urea or uric acid levels in saliva (or blood) [55,56], including: Alcohol addiction [57,58], Ankylosing spondylitis [59], Diverticulosis [60], Gout [56], Hyperlipidemia [61,62], Kidney cyst [63,64], Kidney disease [6567], Pancreatitis [68,69]. “Control” samples are selected from those lacking all disease phenotype labels in the validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, we can do a case/control differential analysis for OralUreaseActivityPathways in our independent validation cohort. Here, “case” samples are defined using an aggregate of multiple systemic disease phenotypes which are based on reported associations to urea or uric acid levels in saliva (or blood) [55,56], including: Alcohol addiction [57,58], Ankylosing spondylitis [59], Diverticulosis [60], Gout [56], Hyperlipidemia [61,62], Kidney cyst [63,64], Kidney disease [6567], Pancreatitis [68,69]. “Control” samples are selected from those lacking all disease phenotype labels in the validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that individuals with a low plaque/bleeding ratio developed significantly more clinical inflammation in terms of bleeding and swelling of the gingiva than individuals with a high plaque/bleeding ratio ( 20 ). The inferior clinical utility of salivary endotoxin activity, compared to subgingival LPS activity, could be explained by the contribution of different sources of LPS (from other oral niches) to the total salivary LPS ( 9 ). In our study, the levels of salivary endotoxin activities did not show statistically significant correlations with subgingival endotoxin activity, suggesting that subgingival niche might not be the main source of salivary LPS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that characteristic lipid A molecular signatures, corresponding to over-acylated, bi-phosphorylated lipid A isoforms, are present in dental plaque and saliva of periodontitis patients. In addition, endotoxin activity levels [measured by the recombinant Factor C (rFC) assay] of subgingival and salivary LPS extracts from periodontitis patients were significantly higher compared to healthy volunteers ( 8 , 9 ). Monitoring endotoxin activity in oral fluids could be a valuable risk assessment tool for primary and secondary prevention of periodontal diseases and personalised treatment choices, giving an opportunity to intervene closer to the biologic onset of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…This has enabled me to explore both the scientific and educational facets required in an academic career, and i have been able to establish research in both of these areas. My scientific research focuses on host-pathogen interactions, and i have been fortunate to work on multiple projects, including development of three-dimensional oral mucosa models, association of subgingival lipid A profiles with periodontal disease From dental nursing to senior academic in dentistry: a personal career journey status, 1,2 and in 2019 i received the Colgate robin Davies Dental Care professional research Award from the oral and Dental research Trust (oDrT), for a project investigating modulation of osteoclast differentiation and activity by endotoxin tolerance. This Dental Care professional (DCp) specific award was instrumental in developing an independent research career and i remain grateful to the oDrT for the opportunity.…”
Section: Career In Dental Research and Educationmentioning
confidence: 99%